Salmon Muscle Adherence to Polymer Coatings and Determination of Antibiotic Residues by Reversed-Phase High-Performance Liquid Chromatography Coupled to Selected Reaction Monitoring Mass Spectrometry, Atomic Force Microscopy, and Fourier Transform Infrared Spectroscopy - E. Zumelzu; M. J. Wehrhahn; O. Muñoz; F. Rull (International Journal of Polymer Science)
The persistent adhesion of salmon muscle to food container walls after treatment with urea solution was observed. This work evaluated the diffusion of antibiotics from the salmon muscle to the polyethylene terephthalate (PET) coating protecting the electrolytic chromium coated steel (ECCS) plates. New aquaculture production systems employ antibiotics such as florfenicol, florfenicol amine, oxytetracycline, and erythromycin to control diseases. The introduction of antibiotics is a matter of concern regarding the effects on human health and biodiversity. It is important to determine their impact on the adhesion of postmortem salmon muscle to can walls and the surface and structural changes affecting the functionality of multilayers. This work characterized the changes occurring in the multilayer PET polymer and steel of containers by electron microscopy, 3D atomic force microscopy (3D-AFM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FT-IR) analyses. A robust mass spectrometry methodology was employed to determine the presence of antibiotic residues. No evidence of antibiotics was observed on the protective coating in the range between 0.001 and 2.0 ng/mL; however, the presence of proteins, cholesterol, and alpha-carotene was detected. This in-depth profiling of the matrix-level elements is relevant for the use of adequate materials in the canning export industry.